“The Incest Plot” in John Banville’s Ancient Light - Karen Anne McCarthy (ABEI Journal, 2023)
Ancient Light (2012), the third and (to date) final book in the Alexander and Cass Cleave series by John Banville, is a text in which characters who died in the previous books are recycled and brought back as roles in a film, played by characters whose characterisation itself blurs with the roles they are playing. Banville’s established preoccupation with returning to the past and retracing old ground takes on an intriguingly excessive dimension in this novel. Ancient Light presents a heightened version of what Neil Murphy has referred to as an “interlocked intertextual Banvillean world” (86). This article will examine the book using Stephanie Insley Hershinow’s ideas around “the incest plot.” She calls this structure a “model of tautological self-enclosure – the embrace of self-sameness, repetition, even redundancy, over change” (150). My claim is that the novel’s very infrastructure is one of “tautological self-enclosure.” The features of “self-sameness, repetition [and] redundancy” are inescapable in this novel, and the “change” conventionally offered by third books in trilogies is simply not to be encountered in Banville’s relentlessly self-referential third instalment. In her discussion of incest as form, Hershinow contends that “highlighting form is the only way to see the ways that incest exceeds its literal manifestations” (156). She further suggests that incest “is a way for the novel to explore the minimal amount of difference required for narrative to continue to function as such, to experiment with narrative minimalism” (ibid.). The plot structure, as well as a more literal interpretation of ‘incest’ will be mined, given that the narrator’s desire for his dead daughter Cass is the primary animating force behind the narrative.